2016
DOI: 10.1007/s00170-015-8303-8
|View full text |Cite
|
Sign up to set email alerts
|

Using spindle noise to monitor tool wear in a turning process

Abstract: A tool condition monitoring system can increase the competitiveness of a machining process by increasing the utilised tool life and decreasing instances of part damage from excessive tool wear or tool breakage. This article describes an inexpensive and non-intrusive method of inferring tool condition by measuring the audible sound emitted during machining. The audio signature recorded can be used to develop an effective in-process tool wear monitoring system where digital filters retain the signal associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 17 publications
(47 reference statements)
0
38
0
Order By: Relevance
“…Wear behavior V B in both test conditions obeys to linear models, with determination coefficients above 0.93. Seemuang et al [21] and Wang et al [13], working on conventional turning processes, reported flank wear behavior similar in shape to a) b)…”
Section: V B Measurements A) Hm Tool B) Hss Toolmentioning
confidence: 80%
See 1 more Smart Citation
“…Wear behavior V B in both test conditions obeys to linear models, with determination coefficients above 0.93. Seemuang et al [21] and Wang et al [13], working on conventional turning processes, reported flank wear behavior similar in shape to a) b)…”
Section: V B Measurements A) Hm Tool B) Hss Toolmentioning
confidence: 80%
“…This indirect wear measurement technique is described by Seemuang et al [21] and Jemielniak et al [22], who show evident changes in surface roughness and mechanical vibrations when the tool wears, mainly since vibrations are a manifestation of variation in cutting forces, and the dimensional and geometric stability of the manufactured pieces are affected by those forces.…”
Section: V B Measurements A) Hm Tool B) Hss Toolmentioning
confidence: 99%
“…The use of stand-off microphones has been demonstrated for TCM in conjunction with other signals [15,16] and alone. [17,18] The omnidirectional nature of microphones gives the capacity to collect a large quantity of data: if different elements of the process produce different frequencies, sound data can capture an overview of the entire process. This can lead to background noise issues because of their unselective nature, meaning post-processing is important.…”
Section: Process Monitoringmentioning
confidence: 99%
“…Thanks to SPM, it is possible to detect production system failures such as collision, overload, breakdown, and tool wear [3]; and thus, it is contributing to saving costs in manufacturing [4]. In this sense, SPM can increase the competitiveness of a machining process by increasing the utilized tool life and decreasing instances of part damage from excessive tool wear or tool breakage [5]. For all these reasons, industries are interested in measuring their product characteristics [6].…”
Section: Introductionmentioning
confidence: 99%